Elemental analysis of the thyroid by laser induced breakdown spectroscopy - Ahmed, Irfan; Ahmed, Rafay; Yang, Jingwei; Law, Alan Wing Lun; Zhang, Yanpeng; Lau, Condon (Biomedical optics express, 2017)
The thyroid is an important hormone regulation organ. Laser induced breakdown spectroscopy (LIBS) is developed to assess iodine and other essential elements in the thyroid (of rats). Subjects are administered 0.05% iodine water for 0, 6, and 12 days before the thyroid is extracted. Pronounced iodine, sodium, calcium, and potassium emissions are observed at approximately 746, 589, 395/422, and 766/770 nm, respectively. Iodine emission is surprisingly highest in 0 day subjects, lowest after 6 days, and recovers by 12 days. This follows the Wolff-Chaikoff effect as ingestion of excess iodine reduces thyroid iodine and iodine is essential for hormone production. LIBS is a promising method for trace elemental analysis of the thyroid.